2017
DOI: 10.1007/s00018-016-2451-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics as regulators of cancer biology

Abstract: Mitochondria are dynamic organelles that supply energy required to drive key cellular processes, such as survival, proliferation, and migration. Critical to all of these processes are changes in mitochondrial architecture, a mechanical mechanism encompassing both fusion and fragmentation (fission) of the mitochondrial network. Changes to mitochondrial shape, size, and localization occur in a regulated manner in order to maintain energy and metabolic homeostasis, while deregulation of mitochondrial dynamics is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
182
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(186 citation statements)
references
References 146 publications
(198 reference statements)
4
182
0
Order By: Relevance
“…In fact, cancer cells frequently show an imbalance of fission and fusion. Accumulating evidence is beginning to provide an increased mechanistic understanding of how mitochondrial dynamics, which reflect the organelles’ exquisite heterogeneity in shape and spatial distribution, affect tumorigenesis and participate in metabolic reprogramming . Consistent with these observations, many studies have shown that the mitochondria‐associated fission protein Drp1 promotes tumor migration and pathogenesis, including in lung cancer, metastatic breast cancer, glioblastoma, colorectal cancer, pancreatic cancers, thyroid tumors, nasopharyngeal carcinoma and melanoma (Table ).…”
Section: Mitochondrial Network Structure Imbalance Is Associated Withmentioning
confidence: 89%
“…In fact, cancer cells frequently show an imbalance of fission and fusion. Accumulating evidence is beginning to provide an increased mechanistic understanding of how mitochondrial dynamics, which reflect the organelles’ exquisite heterogeneity in shape and spatial distribution, affect tumorigenesis and participate in metabolic reprogramming . Consistent with these observations, many studies have shown that the mitochondria‐associated fission protein Drp1 promotes tumor migration and pathogenesis, including in lung cancer, metastatic breast cancer, glioblastoma, colorectal cancer, pancreatic cancers, thyroid tumors, nasopharyngeal carcinoma and melanoma (Table ).…”
Section: Mitochondrial Network Structure Imbalance Is Associated Withmentioning
confidence: 89%
“…The inner mitochondrial membrane is extensively folded, producing invaginations called cristae, which control oxidative phosphorylation (OXPHOS), electron and metabolite transport, and cell death and survival (3). Consequently, mitochondrial network dysregulation is linked to several pathophysiological conditions, including cancer, diabetes, and neurodegenerative diseases (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Conversely, mitochondrial dynamics is controlled by mitochondrion-shaping proteins that regulate fusion and fission events. Core components of the mitochondrial fusion/ fission machinery include mitofusin 1 (MFN1), mitofusin 2 (MFN2), and optic atrophy 1 (OPA1), which promote fusion, whereas fission is governed by dynamin-related protein 1 (DRP1) and by adaptor proteins such as mitochondrial fission factor (MFF), mitochondrial dynamics proteins (MiD49 and MiD51), and fission 1 (FIS1) (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Although most solid tumors obtain their energy from aerobic glycolysis (Warburg effect), mitochondria still play a key role in tumor growth . Active mitochondria favor tumorigenesis, cell migration, metastasis and drug resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Active mitochondria favor tumorigenesis, cell migration, metastasis and drug resistance . By contrast, impairing oxidative phosphorylation in mitochondria decreases cancer cell proliferation and invasion, and triggers apoptosis . Cancer cell mitochondria have higher transmembrane potentials than non‐transformed cells .…”
Section: Introductionmentioning
confidence: 99%